ELIMED-ELIMAIA: The First Open User Irradiation Beamline for Laser-Plasma-Accelerated Ion Beams - Cirrone, Giuseppe A. P.; Petringa, Giada; Catalano, Roberto; Schillaci, Francesco; Allegra, Luciano; Amato, Antonino; Avolio, Renato; Costa, Michele; Cuttone, Giacomo; Fajstavr, Antonin; Gallo, Giuseppe; Giuffrida, Lorenzo; et al. (Frontiers in Physics, 2020)
The main effort of the laser-driven ion acceleration community is aimed to improve particle beam features (energy, charge, divergence, monochromaticity) and to demonstrate reliable approaches to be used for multidisciplinary applications. An ion acceleration target area based on unique laser capabilities is available at ELI-Beamlines (Extreme Light Infrastructure) in the Czech Republic; it is called ELIMAIA (ELI Multidisciplinary Applications of laser-Ion Acceleration) and aims to provide stable, fully characterized and tuneable beams of particles accelerated by multi-Petawatt-class lasers and to offer them to the user community for multidisciplinary applications. The ELIMAIA section dedicated to ion focusing, selection, characterization and irradiation is named ELIMED (ELI MEDical and multidisciplinary applications). Thanks to ELIMED, very high-dose-rate (around Gy/min) controlled proton and ion beams, with energy ranging from 5 to 250 MeV, will be transported up to an in-air section dedicated to absolute and relative dosimetry of the laser-generated ions. A transmission, dual-gap air ionisation chamber will allow an on-line, non-destructive characterization of the ion dose at the user sample irradiation point. The uncertainty in the final dose released onto the sample is expected to be well below 5%. An ELIMED radiobiology pilot experiment is scheduled in 2021, during which in-vitro cell irradiations will be carried out with well-controlled proton beams. In this work, the status of the ELIMED/ELIMAIA beamline will be reported along with a complete description of the main dosimetric systems and of their calibrations carried out at conventional accelerators.